2017
DOI: 10.21082/jpasca.v12n2.2015.93-104
|View full text |Cite
|
Sign up to set email alerts
|

EFIKASI CUKA KULIT PISANG DAN AIR KELAPA SEBAGAI PENGHAMBAT Listeria monocytogenes PADA DAGING AYAM

Abstract: ABSTRAKPenyediaan pengawet alami untuk meningkatkan umur simpan daging ayam merupakan tantangan tersendiri, ditengah maraknya penggunaan pengawet kimia saat ini. Permasalahan kontaminan mikroba telah menjadi perhatian banyak kalangan baik pemerintah, pelaku usaha, konsumen, maupun pemerhati kesehatan. Asam asetat yang dikenal sebagai cuka memiliki sifat sebagai antimikroba, disebabkan kemampuannya menurunkan pH dan menyebabkan instabilitas membran sel pada bakteri patogen. Tulisan ini bertujuan mengkaji pembua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…The Several studies also say that coconut water is able to preserve food ingredients from meat. Widaningrum et al (2015) stated that banana peel vinegar and coconut water were able to preserve chicken meat the same as commercial acetic acid when stored for 12 days. Suara et al (2014) also reported that fermented coconut water ice was able to preserve Cakalang fish.…”
Section: The Effect Of Eco-enzyme In Tomatoesmentioning
confidence: 99%
“…The Several studies also say that coconut water is able to preserve food ingredients from meat. Widaningrum et al (2015) stated that banana peel vinegar and coconut water were able to preserve chicken meat the same as commercial acetic acid when stored for 12 days. Suara et al (2014) also reported that fermented coconut water ice was able to preserve Cakalang fish.…”
Section: The Effect Of Eco-enzyme In Tomatoesmentioning
confidence: 99%
“…Bioavaibilitas merupakan ketersediaan sejumlah logam yang dapat diserap oleh hayati. Semakin tinggi tingkat bioavailabilitas logam berat dalam tanah, semakin tercemar tanaman yang tumbuh pada tanah tersebut (Widaningrum et al, 2007). Bioavailabilitas logi am berat ditentukan dengan metode ekstraksi bertahap.…”
Section: Pendahuluanunclassified
“…There wasn't Cd found in the vegetable samples, it was suspected that the soil in which the vegetable is grown did not contain Cd. In addition, the abundance of Cd in nature is also relatively very small [18]. Cadmium is a heavy metal that has received a lot of attention from the public and the environment.…”
Section: Heavy Metals Concentration In Vegetables Cultivated In Ex-ti...mentioning
confidence: 99%